Strategi Pengelolaan Ekowisata Berbasis Joint Tourism Pada Objek Wisata Sungai Gagak di Desa Koto Mesjid, Kabupaten Kampar, Riau - Doni Sugianto Sihotang; Achmad Hidir (Lasigo Akademia Indonesia, 2022)
This study discusses the strategy for managing the Ecotourism potential of the Gagak River that's located in Koto Mesjid, Kampar. The ecotourism management strategy is based on Joint Tourism, which is managed by youth who are members of the Kelompok Sadar Wisata Pemuda Komppak. This strategy developed through several approaches to market and promote tourism to increase the number of tourists that visit and very suitable to be developed in the Gagak River Ecotourism, considering its location far from settlements and in the forest, so to reach outside tourists, it's necessary to create a strategy that connects the Gagak River with other tourism in Koto Mesjid. The research method used is an ethnographic study in which researchers live in for two months. Data were collected using ethnographic method such as field observations, in-depth interviews, and distributing questionnaires to discover why visitors came to Sungai Gagak. The results of this study indicate that the Joint Tourism-based Gagak River ecotourism management strategy that connects the Gagak River with other tours in Koto Mesjid Village such as Puncak Kompe and Lembah Aman to mutually become the key to the success of Gagak River ecotourism so as to attract daily tourists reaching 50-100/per day..